Proceedings of the 57th Annual Meeting of the Association for Computational Linguistics 2019
DOI: 10.18653/v1/p19-1273
|View full text |Cite
|
Sign up to set email alerts
|

Who Sides with Whom? Towards Computational Construction of Discourse Networks for Political Debates

Abstract: Understanding the structures of political debates (which actors make what claims) is essential for understanding democratic political decision-making. The vision of computational construction of such discourse networks from newspaper reports brings together political science and natural language processing. This paper presents three contributions towards this goal: (a) a requirements analysis, linking the task to knowledge base population; (b) a first release of an annotated corpus of claims on the topic of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Particularly helpful for high recall was the integration of ML-based pseudo-annotators: the identification of claims is a hard task for human coders, so that even the merging of several independent human annotations does not guarantee full coverage. We found that relatively simple neural sequence classifiers were already good enough to substantially boost the recall during the merging phase (Padó et al, 2019).…”
Section: Usability Studymentioning
confidence: 86%
See 2 more Smart Citations
“…Particularly helpful for high recall was the integration of ML-based pseudo-annotators: the identification of claims is a hard task for human coders, so that even the merging of several independent human annotations does not guarantee full coverage. We found that relatively simple neural sequence classifiers were already good enough to substantially boost the recall during the merging phase (Padó et al, 2019).…”
Section: Usability Studymentioning
confidence: 86%
“…In this section, we show how MARDY has been employed in a political science study targeting one of the major topics of German politics of 2015: the domestic debate on (im)migration policy. So far, we annotated 423 newspaper articles from TAZ (http://www.taz.de/), with a total of 982 claims (Padó et al, 2019).…”
Section: Usability Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Within NLP, such efforts tend to focus more on describing how language differs between political subgroups, rather than recognizing similarities in denotation across ideological stances, which is the primary goal of our work. For example, Preoţiuc-Pietro et al (2017); Han et al (2019) attempt to predict a person's political ideology from their social media posts, Sim et al (2013) detect ideological trends present in political speeches, Fulgoni et al (2016) predict political leaning of news articles, and Padó et al (2019) focuses on modeling the network structure of policy debates within society. Also highly related is work analyzing linguistic framing in news (Greene and Resnik, 2009;Choi et al, 2012;Baumer et al, 2015).…”
Section: Related Workmentioning
confidence: 99%
“…The second line of research targets the direct automatic analysis of politic debates in textual form. As far as political claim analysis in newspaper articles is concerned, Padó et al (2019) have developed relatively simple embedding-based models for claim identification and classification. The experiments presented in this paper are based on their model architecture.…”
Section: Related Work: Debate and Manifestosmentioning
confidence: 99%